2019
DOI: 10.1007/s11136-019-02228-3
|View full text |Cite
|
Sign up to set email alerts
|

Appraising the quality of tools used to record patient-reported outcomes in users of augmentative and alternative communication (AAC): a systematic review

Abstract: PurposePeople who have complex communication needs (CCN), and who use augmentative and alternative communication (AAC) to help them express themselves, can be difficult to engage in decision making about their healthcare. The purpose of this review was to identify what patient-reported outcome measures (PROMs) have been employed with people who use AAC. Of the tools identified, the review aimed to establish what conceptual frameworks were used and how the reports describe completion of the PROM.MethodsA system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The limited data collected from people from people with IDD in population health and QoL research have major implications for describing health characteristics and needed supports in this population (Broomfield et al, 2019). We believe that concerns about the reliability and validity of self-report in IDD are also shaped by expectations resulting from the disability paradox and beliefs about the ability of people with IDD to meaningfully report on their health and QoL outcomes.…”
Section: Implications: Emerging Directions In Self-reporting Of Health In Iddmentioning
confidence: 99%
See 2 more Smart Citations
“…The limited data collected from people from people with IDD in population health and QoL research have major implications for describing health characteristics and needed supports in this population (Broomfield et al, 2019). We believe that concerns about the reliability and validity of self-report in IDD are also shaped by expectations resulting from the disability paradox and beliefs about the ability of people with IDD to meaningfully report on their health and QoL outcomes.…”
Section: Implications: Emerging Directions In Self-reporting Of Health In Iddmentioning
confidence: 99%
“…Many factors contribute to under-utilization of self-reported health outcomes measures in people with IDD including concerns about (1) the reliability and validity of self-reporting and (2) the burden of participation in this population (Broomfield, Harrop, Judge, Jones, & Sage, 2019;Felce & Perry, 1995;Finlay & Lyons, 2001;Fujiura & the RRTC Expert Panel on Health Measurement, 2012). A common strategy to address these challenges has involved the use of proxy-reporting by supporters to assess the health and QoL of people with IDD (Cella et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and AAC method (e.g., unaided AAC (body movements, gestures, facial expressions, signs); aided AAC (objects, object symbols, photographs, picture symbol boards and books; communication devices). The formulation of AAC was based on the recently conducted studies and systematic reviews (30,31) . AAC interventions had to be provided individually or in a group and conducted by a speech therapist (or an aligned specialist) working in specialized centers and departments (special education center, a local primary care facilities, schools or preschool centers, office of a speech therapist, a hospital speech therapy department).…”
Section: Types Of Interventionsmentioning
confidence: 99%
“… 24 Although an increasing trend towards participatory research designs can be observed, most larger surveys in this area still rely on proxy respondents. One reason for this is likely the fact that there are no tools for patient-reported outcome measures (PROMs) specifically designed for people who use AAC, as Broomfield et al 25 found out in their systematic review. On the one hand, it is extremely important to develop such PROMs for people who use AAC, and on the other hand and regarding the current situation, it is also very important to consider potential factors influencing proxy reporting.…”
Section: Introductionmentioning
confidence: 99%